Social, environmental, and corporate governance (ESG): Historical perspectives and key changes in organizations - Silva, Cássia Mara Alexandrino; Filho, Teodoro Antunes Gomes; Rebello, Flávia Adriana Santos; Fonseca , Marcello Pires; Sebastiani, Rafael Teixeira; Junior , Antonio Pereira da Silva; Santos, Franque da Conceição dos; Veloso, Christiane Carvalho; Marques, Francisco Roldineli Varela; Santos, Gilvan Duarte dos; Conceição, Thabata Bispo; Carvalho , Ana Luisa Gordiano de (Seven Editora, 2024)
The objective of this research was to analyze the historical perspectives of social, environmental and corporate governance (ESG) and the main changes in organizations. This was an integrative literature review.  Data were collected through a survey of the Google Scholar and Scielo databases, using specific keywords and search criteria in conciliation with the descriptors "AND" and "OR". Analyses of corporate sustainability and environmental compliance show their growing importance in the contemporary business scenario. Environmental compliance emerges as an essential tool to ensure compliance with environmental standards, mitigate legal risks and promote ethical management. These approaches reflect a paradigm shift in business practices, prioritizing social and environmental impact. By taking a holistic view, businesses can improve their financial performance and contribute to sustainable development. Despite the challenges in implementing compliance and sustainable practices, the benefits are evident, strengthening credibility, attracting investors aligned with corporate values and ensuring long-term success in an increasingly conscious context on social and environmental issues. DOI:https://doi.org/10.56238/sevened2024.010-008